Precisely Controlled Integration of Multiple Metal Cations in Diverse Metal‐Organic Framework Topologies via Messenger Building Unit Approach - Clara López‐García; Alina A. Skorynina; Fátima Esteban‐Betegón; Javier Pérez‐Carvajal; Marta Iglesias; M. Angeles Monge; Enrique Gutiérrez‐Puebla; Felipe Gándara (Small Structures, 2025)
Achieving precisely controlled multimetal configurations in the structure of metal‐organic frameworks (MOFs) through one‐pot reactions remains a synthetic challenge. The use of heterometallic molecular clusters as messenger building units (mBUs) is recently reported as a feasible approach to address this issue in the formation of MOFs with sra topology. Herein, the successful expansion of this approach is reported to achieve MOFs with distinct topologies through the use of linkers with different connectivities, such as the tritopic 1,3,5‐tris(4‐carboxyphenyl)benzene (H3BTB) and the tetratopic tetrakis(4‐carboxyphenyl)porphyrin, (H6TCPP). The reaction of Ga7M mBU (M = Ni, Co) with H3BTB and H6TCPP yields porous MOFs Ga2M‐BTB and Ga7M‐TCPP, with sit and fry topology, respectively. The MOFs incorporate the initially selected metal combinations in their inorganic secondary building units, as demonstrated by the use of X‐ray diffraction, X‐ray spectroscopies, electron microscopy, and gas sorption techniques. It is also shown that alginate‐based bead shaped composites can be formed with Ga7M‐TCPP MOFs, and are efficient heterogeneous photocatalysts, as demonstrated with their use in the aza‐Henry reaction, showing improvements in activity and selectivity as compared with single‐metal analogues.